Icariin Has a Synergistic Effect on the Osteoinductivity of Bone Morphogenetic Protein 2 at Ectopic Sites - Xin Zhang; Xingnan Lin; Mingjie Wang; Liquan Deng; Lingfei Wei; Yuelian Liu (Orthopaedic Surgery, 2023)
Objective Establishing biocompatible, biodegradable, osteoconductive, and osteoinductive bone materials remains a challenging subject in the research of bone healing and bone regeneration. Previously, we demonstrated the osteogenic and osteoconductive effects of biomimetic calcium phosphate (BioCaP) incorporating with Icariin and/or bone morphogenetic protein 2 (BMP‐2) at orthotopic sites. Methods By implanting the BioCaP granules incorporated Icariin and/or BMP‐2 into the dorsal subcutaneous pockets of adult male Sprague‐Dawley (S‐D) rats (6‐7 weeks old), we investigated the osteoinductive efficacy of the samples. Micro‐computed tomography(micro‐CT) observations and histological slices were used to verify the osteoinduction of this system on the 2nd and 5th week. Statistical significances was evaluated using Turkey's post hoc test of one‐way analysis of variance. Results The osteoinduction of the BioCaP incorporated with BMP‐2 or both agents was confirmed as expected. BioCaP with Icariin alone could not generate bone formation at an ectopic sites. Nevertheless, co‐administration of Icariin increased bone mineral density (BMD; p < 0.01) (628mg HA/cm3 vs 570mg HA/cm3) and completely changed the distribution of newly formed bone when compared with the granules with BMP‐2 alone, even though there was no significant difference in the volume of newly formed bone. In contrast, the BioCaP with both agents (37.86%) had significantly fewer remaining materials than the other groups by the end of the fifth week (53.22%, 53.62% and 48.22%) (p < 0.01). Conclusion The co‐administration of Icariin and BMP‐2 increased BMD changed the distribution of newly formed bone, and reduced the amount of remaining materials. Therefore, Icariin can stimulate BMP‐2 when incorporated into BioCaP granules at ectopic sites, which makes it useful for bone tissue engineering.